Pengaruh Sosial Ekonomi, Produktivitas Pekebun, dan Manajemen Usaha Tani terhadap Keputusan Pengembangan Usaha Tani Kelapa Sawit Rakyat (Studi pada Perkebunan Kelapa Sawit di Kabupaten Keerom Provinsi Papua) - Huwae, Rory Cony; Idrus, M.S; Salim, Ubud (Jurnal Aplikasi Manajemen, 2013)
The purpose of this study is to analyze empirically: 1) whether socio economic influence ondevelopment decisions palm farming people, 2) whether socio economic effect on farm management, 3)whether the socio-economic impact on the productivity of planters, 4) whether the productivity of planterseffect on farm management, 5) whether the productivity of planters influence on development decisionspalm farming folk, and 6) how to influence farm management decisions of the development of oil palmfarming folk. The research method used is a mixed approach design format (mixing approach). Location ofresearch on oil palm plantations in Keerom District, Papua Province. Total observational deep populationit as much 200 farmers or oil palm people gardens on kampong/sub-district at Regency Keerom, PapuaProvince. Sample that is utilized as much 200 person pekebun little or oil palm people gardens on kampong/sub-district at Regency keerom, Papua province. The results showed that: 1) the influence of socioeconomicvariables on the decision of the development of oil palm farming folk who do not have a significant relationshipwith the effect of path coefficients (direct effects) amounted to 0.049, the indirect effects (indirecteffects) of 0358, and²- value 0.647. 2) the influence of socioeconomic variables on farm management hada significant relationship with the effect of path coefficients (direct effects) amounted to 0.426, the indirecteffects (indirect effects) of 0168, and²-value < 0.001. 3) socio-economic impact on the productivity ofplanters who did not have a significant relationship with the effect of path coefficients (direct effects)amounted to 0.166, the indirect effects (indirect effects) = 0.000, and²-value 0.252. 4) influence theproductivity of planters on business management farmer has a significant relationship with the influence ofa direct effects path coefficients (direct effects) amounted to 0.482, the indirect effects (indirect effects) of0187, and²-value < 0.001. 5) the influence of productivity planters against the decision of oil palm farmingbusiness development people have significant correlation with the effect of path coefficients (direct effects)amounted to 0.396, the indirect effects (indirect effects) of 0409, and²-value < 0.002. 6) the influence offarm management decisions of the development of oil palm farming people have relationships significantwith the effects of the direct path coefficient (direct effects) amounted to 0.498, the indirect effects (indirecteffects) of 0187, and²-value < 0.001.